Wykorzystanie informacyjnych walorów rachunkowości finansowej w nowoczesnym zarządzaniu controllingowym - Lew, Grzegorz (The Use of Informative Advantages of Financial Accountancy in Modern Controlling Management, 2006)
The paper is tempting to show high possibilities of an integration of financial accountancy and management for managers. In the paper there are featured some possibilities of the connection of information from the financial accountancy with the motivation of sales representatives in enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 299-306